Catalogue of snout mites (Acariformes: Bdellidae) of the world - Hernandes, Fabio A. [UNESP]; Skvarla, Michael J.; Fisher, J. Ray; Dowling, Ashley P. G.; Ochoa, Ronald; Ueckermann, Edward A.; Bauchan, Gary R. (Magnolia Press, 2016)
Bdellidae (Trombidiformes: Prostigmata) are moderate to large sized predatory mites that inhabit soil, leaves, leaf litter, and intertidal rocks. They are readily recognized by an elongated, snout-like gnathosoma and by elbowed pedipalps bearing two (one in Monotrichobdella Baker & Balock) long terminal setae. Despite being among the first mites ever described, with species described by Carl Linnaeus, the knowledge about bdellids has never been compiled into a taxonomic catalogue. Here we present a catalogue listing 278 valid species; for each species we include distribution information, taxonomic literature, and type depository institutions. The genus Rigibdella Tseng, 1978 is considered a junior synonym of Cyta von Heyden, 1826, and Bdellodes Oudemans, 1937 is considered a junior synonym of Odontoscirus Tohr, 1913. Illustrated keys to subfamilies and genera are presented, as well as keys to species of each genus.
Keywords: mite; Eupodina; Bdelloidea; systematics; taxonomy; biodiversity; predatory mites; predators; soil mites